The impact of walking devices on kinematics in patients with spastic bilateral cerebral palsy - Krautwurst, Britta; Dreher, Thomas; Wolf, Sebastian Immanuel (Gait & posture, 2016)
Increased anterior pelvic and trunk tilt is a common finding in patients with bilateral cerebral palsy especially during walking with assistive devices. As previous studies demonstrate various gait alterations when using assistive devices, the assessment of surgical interventions may be biased when the patients become independent of (or dependent on) assistive devices after therapy. Furthermore, some of these patients in fact are able to walk without devices even though in daily life they prefer to use them. Consequently, for such patients the classification into GMFCS level II or III may be ambiguous. The specific aim of this study was therefore to assess the influence of the use of forearm crutches and posterior walker during walking and to set this influence in relation to outcome effects of surgical intervention studies. 26 ambulatory patients with spastic bilateral CP (GMFCS II-III) were included who underwent 3D gait analysis. All patients used forearm crutches or posterior walkers in everyday life even though they were able to walk without assistive devices for short distances. Independent of the type of assistive devices, the patients walk on average with more anterior trunk tilt and pelvic tilt (7°±6° and 3°±2°) and with a maximum ankle dorsiflexion decreased by 2° (±3°) when walking with assistive devices, enhancing the mal-positioning present without device. Oppositely, the knees on average are more extended by 6° (±4°) when using the assistive devices. These effects have to be taken into account when assessing gait patterns or when monitoring the outcome after intervention as assistive devices may partially hide or exaggerate therapeutic effects.
Gesehen am 25.10.2019